Being nice with the experimenter? - Caterina Giannetti; Raimondello Orsini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2013)
This paper investigates the determinants of reciprocity towards the experimenters in the lab under a flat-wage scheme. We find that personality attributes – such as agreeableness – help predict the behaviour of the subjects. We additionally propose and assess a general measure of reciprocity.
Keywords: C91; J33; 330